Heterogeneity, pore pressure, and injectate chemistry: Control measures for geologic carbon storage. (January 2018) - Dewers, Thomas; Eichhubl, Peter; Ganis, Ben; Gomez, Steven; Heath, Jason; Jammoul, Mohamad; Kobos, Peter; Liu, Ruijie; Major, Jonathan; Matteo, Ed; Newell, Pania; Rinehart, Alex; et al.
Highlights: Control measures for geologic carbon storage are proposed to overcome challenges to efficient storage and injectivity. Injectate chemistry can be used as a measure for fracture stimulation in some reservoirs. Brine withdrawal can control pore pressure hazards, but must account for reservoir heterogeneity. Validated coupled numerical models predict fracture development for reservoir stimulation and to avoid unwanted consequences. Wellbore integrity can be threatened by injection, and must be mitigated, for example by introduction of repair materials. Abstract: Desirable outcomes for geologic carbon storage include maximizing storage efficiency, preserving injectivity, and avoiding unwanted consequences such as caprock or wellbore leakage or induced seismicity during and post injection. To achieve these outcomes, three control measures are evident including pore pressure, injectate chemistry, and knowledge and prudent use of geologic heterogeneity. Field, experimental, and modeling examples are presented that demonstrate controllable GCS via these three measures. Observed changes in reservoir response accompanying CO2 injection at the Cranfield (Mississippi, USA) site, along with lab testing, show potential for use of injectate chemistry as a means to alter fracture permeability (with concomitant improvements for sweep and storage efficiency). Further control of reservoir sweep attends brine extraction from reservoirs, with benefit for pressure control, mitigation of reservoir and wellbore damage, and water use. State-of-the-art validated models predict the extent of damage and deformation associated with pore pressure hazards in reservoirs, timing and location of networks of fractures, and development of localized leakage pathways. Experimentally validated geomechanics models show where wellbore failure is likely to occur during injection, and efficiency of repair methods. Use of heterogeneity as a control measure includes where best to inject, and where to avoid attempts at storage. An example is use of waste zones or leaky seals to both reduce pore pressure hazards and enhance residual CO2 trapping.